Clinical Aspect of Ankylosing Spondylitis - Vinall, Phil (MD Conference Express, 2006)
In ankylosing spondylitis (AS) the relationship between clinical disease activity and signs of the disease as shown by imaging tools, is still very unclear. This article discusses 2 clinical trials for the treatment of AS.